KAJIAN POTENSI ENERGI ANGIN KABUPATEN KAIMANA PROVINSI PAPUA BARAT - Elias K. Bawan (FMIPA Universitas Papua, 2007)
The human needs for electrics energy, especially in Kaimana regency is increasing together with city development and increasing of the resident. The electric energy supply from diesel power plant in PT. PLN (Persero) is very limited, electrical distinguishing and electrical black out are frequently happened. The potential of renewable energy like wind power is very potential to be developed as electrical energy source. Result of the study shows that the average of wind speed is 4.68 metres/second and it can be classified in third class energy. The potential of wind power in Kaimana regency is 267.7 Watt for diameter 2m and 415.60 Watt for diameter 3m.